1700 Using Intra-Operative Imaging as A Tool to Provide Peer Review, Scoring, Feedback and Education for Hand and Wrist Trauma Cases - A Quality Improvement Project. (12th October 2021) - Smith, A; Thompson, A; Stanier, P; Rooker, J; Lowdon, I
Abstract: Aim: To improve the efficiency of intraoperative hand trauma x-ray review, introduce a scoring system for quality of fixation achieved and use this as an education and feedback tool for trainees. Method: A large QI project in 2019 demonstrated that intra-operative images taken using the mini C-arm were not being reviewed. In March 2020 the first QI cycle introduced an Access database to ensure that as cases were removed from the trauma board, they were added to a review list. Each x-ray was also scored in the trauma meeting (good, acceptable, poor) to assess the radiographic quality of fixation. The second QI cycle identified the named surgeon for each case, allowing surgeon specific feedback. Finally, we trained all qualified users of the mini C-arm to upload their own images after each case, reducing the mean time to upload. Results: This QI project has improved the review rate of mini C-arm images from 30% to 100% and every x-ray is scored. The mean time to review images has reduced from 4 days to less than 24 hours. All trainees can access their scores for imaged hand and wrist trauma and receive written constructive feedback. Conclusions: This project ensures appropriate and prompt review of all hand and wrist trauma cases allowing early identification of any concerns. All x-rays are scored, and this process acts as an educational prompt in the trauma meeting. A final report can be printed for each trainee which can be uploaded to their portfolio to document their surgical progress.